2019
DOI: 10.1210/jc.2018-01471
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Deregulation of Protocadherin PCDHGC3 in Pheochromocytomas/Paragangliomas Associated With SDHB Mutations

Abstract: Context SDHB mutations are found in an increasing number of neoplasms, most notably in paragangliomas and pheochromocytomas (PPGLs). SDHB-PPGLs are slow-growing tumors, but ∼50% of them may develop metastasis. The molecular basis of metastasis in these tumors is a long-standing and unresolved problem. Thus, a better understanding of the biology of metastasis is needed. Objective This study aimed to identify gene methylation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…More importantly, among the SDHB-mutated PPGLs, those having a metastatic behavior had a significantly higher levels of methylation than tumors that had not developed metastasis at the last follow-up date. Analysis of the RNAseq data confirmed the epigenetic silencing of, not only PCDHGC3 [24], but also PCDHGC4 gene ( Figure 5). The PCDHGC4 mRNA levels were found significantly decreased in SDHx-mutated PPGLs as compared with tumors with other genotypes.…”
Section: Long-range Hypermethylation Of Clustered Protocadherin Genesmentioning
confidence: 59%
See 3 more Smart Citations
“…More importantly, among the SDHB-mutated PPGLs, those having a metastatic behavior had a significantly higher levels of methylation than tumors that had not developed metastasis at the last follow-up date. Analysis of the RNAseq data confirmed the epigenetic silencing of, not only PCDHGC3 [24], but also PCDHGC4 gene ( Figure 5). The PCDHGC4 mRNA levels were found significantly decreased in SDHx-mutated PPGLs as compared with tumors with other genotypes.…”
Section: Long-range Hypermethylation Of Clustered Protocadherin Genesmentioning
confidence: 59%
“…To identify epigenetic alterations relevant for metastasis, we recently performed a comprehensive analysis of DNA methylation in metastatic PPGLs with and without SDHB mutations. This analysis revealed that over 1000 genes harbored promoter hypermethylation in the metastatic tumors but not in the not metastatic ones thus suggesting that those gene alterations have a role in the pathogenesis of the metastatic disease linked to SDHB mutations [24]. About 15% of these alterations had been also identified in sdhb−/− mouse chromaffin cells and in 41% of SDHx-mutated PPGLs analyzed by Letouzé et al [14].…”
Section: Outline Of the Epigenetic Changes Induced By Abnormal Succinmentioning
confidence: 93%
See 2 more Smart Citations
“…In recent years, genetic changes in PCPG have received increasing attention, and mutations or loss of genes encoding succinate dehydrogenase (SDH) are clinically important genetic changes [4,5], which are associated with the increased metastatic rate of human PCPG. It has been proved that the pathogenesis of nonfamilial PCPG involves SDHB mutation-associated PCPG pro-cadherin c-C3 (PCDHGC3) gene promoter methylation [6] as well as EPAS1 mutations encoding HIF2α [7]. Given that those genetic changes play important roles in the development of PCPG, identification of the genes with a key role in PCPG could be beneficial to the diagnosis, treatment, and prognostic prediction of this neoplasm.…”
Section: Introductionmentioning
confidence: 99%